2007
DOI: 10.1080/02652030701439543
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide in fried and roasted potato products: A review on progress in mitigation

Abstract: The workshop of the European Commission and the Confederation of the Food and Drink Industries of the European Union (CIAA) held in March 2006 in Brussels, Belgium, discussed the key knowledge and achievements in the mitigation of acrylamide. This paper presents the progress made by the potato sector and identifies areas for future research. Because of the important contribution of potato products to acrylamide intake, it is an area that has received much attention. The discovery of the method of formation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 27 publications
0
51
0
1
Order By: Relevance
“…This means that potatoes stored over the winter season and processed in spring may have higher acrylamide content than potato products processed immediately after harvesting. Storage of tubers at higher temperatures reduces sugar levels (Foot et al, 2007). In the present study, a significant difference in mean acrylamide content could not be identified for the general potato group, however, for "French fries" the geometric mean acrylamide content was significantly higher for products sampled between January and June (246 µg/kg), compared to products sampled between July and December (201 µg/kg).…”
Section: Potato Productsmentioning
confidence: 45%
See 2 more Smart Citations
“…This means that potatoes stored over the winter season and processed in spring may have higher acrylamide content than potato products processed immediately after harvesting. Storage of tubers at higher temperatures reduces sugar levels (Foot et al, 2007). In the present study, a significant difference in mean acrylamide content could not be identified for the general potato group, however, for "French fries" the geometric mean acrylamide content was significantly higher for products sampled between January and June (246 µg/kg), compared to products sampled between July and December (201 µg/kg).…”
Section: Potato Productsmentioning
confidence: 45%
“…As indicated by the Union of the European Potato Processing Industry (UEITP), Foot et al (2007) The acrylamide content in French fries are still several times above what seems to be achievable with potatoes low in reducing sugars and the use of low final oil temperatures. The median acrylamide content in 147 samples from restaurants in the area of Zurich was 76 µg/kg after following some simple instructions (Foot et al, 2007).…”
Section: Potato Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first occurrence of ACR in foods, several researchers have demonstrated the significance of variety and cultivar selection on the formation of ACR [103]. Amrein et al [29] found a 50-fold variation in total reducing sugars in the different potato cultivars the authors studied.…”
Section: Agronomic Factorsmentioning
confidence: 99%
“…The study of acrylamide formation has been performed on several vegetable oils (Morgan, 1942;Foot et al, 2007). Acrylamide is classified as probably carcinogenic to humans by the International Agency for Research on Cancer (IARC) (IARC, 1994).…”
Section: Brief On the Health Effects Of Palm Oilmentioning
confidence: 99%